Challenges in Developing National Unity and Governance in Nepal - Guragain, Govinda Prasad (Creative Vision: Multidisciplinary Journal of PMC, 2025)
This article explores the challenges of nation-building in Nepal, highlighting the issues arising from its diverse, multi-cultural, multi-ethnic, multi-religious, and multi-lingual society. The primary focus of the research is on the conflicts driven by this diversity, which pose significant obstacles to nation-building. The study draws on reliable data, statistical evidence, and historical records from credible sources. It employs a qualitative research approach, using descriptive and analytical methods to reach its conclusions. The research also considers the roles of customs, religions, and cultural practices in the nation-building process. The article addresses key areas of inequality in Nepal and examines the underlying causes of these disparities. It emphasizes the need for effective management of conflicts and inequalities to integrate diverse groups into the mainstream of nation-building, a crucial aspect for many nations today. Numerous studies have examined popular participation and political inclusion in Nepal, particularly focusing on the ethnicization of politics and identity movements in recent decades. However, due to conflicts and misunderstandings among political parties, these issues have not been effectively addressed. This lack of resolution poses significant obstacles to nation-building, as many parties exploit these issues for electoral gains rather than seeking genuine solutions. Political stability is another critical aspect of nation-building, and eliminating political instability is essential for establishing a cohesive framework.